1981
DOI: 10.1152/ajprenal.1981.240.1.f70
|View full text |Cite
|
Sign up to set email alerts
|

Calcium in the control of renin secretion: Ca2+ influx as an inhibitory signal

Abstract: The mechanism for the inhibition of renin secretion in vitro from renal cortical slices by angiotensin II, antidiuretic hormone, ouabain, and high K+ concentration was studied. The inhibitory effect of these agents was blocked by a Ca antagonist, verapamil. In addition, epinephrine stimulated renin secretion and its stimulatory action was blocked by ouabain. These results support the hypothesis that Ca2+ influx into juxtaglomerular cells plays a role as an inhibitory signal whereas Ca2+ efflux is a stimulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 0 publications
2
31
0
Order By: Relevance
“…1). We and others have shown that the inhibitory effect of these agents could be attenuated or even be abolished by calcium channel blockers such as verapamil [15,45,59]. Taken together, all of the findings mentioned above are supportive of the idea that the rate of renin release from the juxtaglomerular cells is inversely related to the calcium concentration in the juxtaglomerular cells.…”
Section: Role Of Calcium In the Intracellular Control Of Renin Releasesupporting
confidence: 61%
See 1 more Smart Citation
“…1). We and others have shown that the inhibitory effect of these agents could be attenuated or even be abolished by calcium channel blockers such as verapamil [15,45,59]. Taken together, all of the findings mentioned above are supportive of the idea that the rate of renin release from the juxtaglomerular cells is inversely related to the calcium concentration in the juxtaglomerular cells.…”
Section: Role Of Calcium In the Intracellular Control Of Renin Releasesupporting
confidence: 61%
“…Therefore ouabain leads to an accumulation of calcium within the cell and in consequence to a rise in the intracellular calcium concentration. Ouabain has been found to inhibit renin release [14,29,49,58,59] and additional evidence was obtained to show that this inhibition is a calcium dependent process [14,25,58]. Inhibition of the calcium ATPase by vanadate also inhibits part of the extrusion of calcium and therefore leads to a rise in the intracellular calcium concentration [56].…”
Section: Role Of Calcium In the Intracellular Control Of Renin Releasementioning
confidence: 98%
“…30 Verapamil does not increase catecholamine synthesis, but reduces the postganglionar synthesis of noradrenaline 31 with a beneficial effect on LVH development. Moreover, some other mechanisms may be involved in the reduction of LVH by V, as its effect on the renin-angiotensinaldosterone axis by interfering with the calcium metabolism in the distal convoluted tubule [32][33][34] or decreasing the collagen content was seen in hypertensive rats. 35 Systolic function was not substantially modified by either treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Churchill and M.C. Churchill 1982a), and this inhibition has been shown to be a calcium-dependent process (Park and Malvin 1978;P. C. Churchill 1979;Cruz-Soto et al 1984).…”
Section: Calciummentioning
confidence: 99%
“…Therefore, ouabain leads to an accumulation of calcium within the cell and consequently to a rise in the intracellular calcium concentration. Ouabain has been found to inhibit renin release (Lyons and Churchill 1974;Park and Malvin 1978;P.C. Churchill 1979;Part et al 1981; P.C.…”
Section: Calciummentioning
confidence: 99%